Alkali metal storage mechanism in organic semiconductor of perylene-3,4,9,10-tetracarboxylicdianhydride - Lian, Xu (2022)
Organic semiconductor-based electrode materials are promising candidates for energy storage devices due to their high capacity, excellent flexibility, low cost and resource sustainability. The alkali metal storage mechanisms on various active functional groups of the organic materials, however, are still not clear at the molecular scale. It is essential to conduct systematic mechanism studies for the alkali storage behaviors in organic electrode materials. Here, the chemical and electronic structure evolutions upon the deposition of lithium (Li) and sodium (Na) on a model organic semiconductor electrode material of perylene-3,4,9,10-tetracarboxylicdianhydride (PTCDA), have been investigated by in-situ x-ray photoemission spectroscopy (XPS), ultraviolet photoelectron spectroscopy (UPS), near edge x-ray absorption fine structure (NEXAFS) spectroscopy and density functional theory (DFT) calculations. It reveals that Li/Na can react with the carbonyl oxygen and increase the electron density within the PTCDA perylene. Moreover, the band-bending like features are observed on PTCDA film upon Li/Na interaction. Our experimental results and theoretical calculations indicate that reactions on carbonyl groups and charge redistribution are crucial for the Li/Na storage process, which shed light on comprehensive insights for the Li/Na storage behaviors on organic semiconductor-based electrode materials.